Tuberculosis drug resistance isolates from pulmonary tuberculosis patients, Kassala State, Sudan. Issue 1 (March 2015) - Khalid, Fatima A.; Hamid, Zuhal A.; Mukhtar, M.M.
Abstract Background This study was conducted in Kassala Teaching Hospital, Kassala State, Sudan (January 2006–June 2008) to determine the rate of mycobacterium drug resistance to anti-tuberculous treatment and to explore the genotype of Mycobacterium tuberculosis resistant isolates using rpoB gene. Methods 53 isolates of mycobacterium isolated from pulmonary tuberculosis (PTB) patients from Kassala State were subjected to drug susceptibility testing (DST) to anti-tuberculous drugs; 10 M.tuberculosis complex (MTBC) resistant isolates were subjected to polymerase chain reaction (PCR), and commercially the amplified DNA was sequenced. Results DST detected resistance in 23/53 (43.39%) isolates, among which rifampicin had a high number of resistant isolates (13/23), followed by streptomycin (11/23), and multi-drug resistance was detected in 5 isolates. DNA sequence analysis of 10 MTBC-resistant isolates detected variations within and outside the rifampicin resistant determining region (RRDR). Variation within RRDR was detected at positions 512 (AGC/ATC, Ser/Ile), and 528 (CGC/CTC, Arg/Leu). Outside the RRDR region variations were detected at positions 498 (GTG/GGG, Val/gly), 488 (ACA/ACC, Thr/Thr), which is a silent mutation. Insertions were observed at positions 484, 496 (GTG/GTGA, CGG/CAGG, respectively). Deletion was observed at position 487 (ATC/_TC). Discussion and conclusion This study revealed that high resistance to rifampicin was associated with various point mutations in and out of the RRDR of the rpoB gene. Molecular methods are needed for early detection of TB disease and drug resistance.